2023
DOI: 10.1073/pnas.2221284120
|View full text |Cite
|
Sign up to set email alerts
|

Simple optical nanomotion method for single-bacterium viability and antibiotic response testing

Abstract: Antibiotic resistance is nowadays a major public health issue. Rapid antimicrobial susceptibility tests (AST) are one of the options to fight this deadly threat. Performing AST with single-cell sensitivity that is rapid, cheap, and widely accessible, is challenging. Recent studies demonstrated that monitoring bacterial nanomotion by using atomic force microscopy (AFM) upon exposure to antibiotics constitutes a rapid and highly efficient AST. Here, we present a nanomotion detection method based on optical micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The microfluidic device used as an analysis chamber can be manufactured on the spot in less than 5 min and does not require any specialized instrumentation (nor a clean room), except the 5-μm-thick double-faced rubber tape and a desk paper punch. Very basic low-cost optical microscopes can be used as imaging devices ( Villalba et al, 2023 ), and if required, the imaging camera can be replaced by a mobile phone. Contrary to the previous ONMD sensitivity testing method, no sophisticated cell tracking computer software is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microfluidic device used as an analysis chamber can be manufactured on the spot in less than 5 min and does not require any specialized instrumentation (nor a clean room), except the 5-μm-thick double-faced rubber tape and a desk paper punch. Very basic low-cost optical microscopes can be used as imaging devices ( Villalba et al, 2023 ), and if required, the imaging camera can be replaced by a mobile phone. Contrary to the previous ONMD sensitivity testing method, no sophisticated cell tracking computer software is required.…”
Section: Discussionmentioning
confidence: 99%
“…These two parameters seriously limit the applicability of the technique on a larger scale. In order to overcome these limitations, we recently demonstrated that simple optical microscopes can achieve nanomotion detection by using sophisticated image processing algorithms that monitor fungal or bacterial displacements with a sub-pixel resolution ( Willaert et al, 2020 ; Villalba et al, 2023 ). In this case, single bacterium or yeast cell displacements are tracked using optical microscopy in a timeframe of approximately 10 s as a function of time after exposure to chemicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the primary and most straightforward applications is the development of rapid and label-free antimicrobial sensitivity tests for pathogenic bacteria (or yeasts) ( Stupar et al, 2017 ; Mustazzolu et al, 2019 ; Villalba et al, 2022 ; 2023 ; Radonicic et al, 2023 ). In this approach, the organism of interest is exposed to different antibiotics, and its nanomotion is monitored over time.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular nanomotion was highlighted for the first time by attaching living cells to an AFM cantilever and monitoring its oscillations. More recently, our team demonstrated that traditional optical microscopes equipped with a video camera and dedicated software can also detect bacterial [31], fungal [32,33], and mitochondrial [34] nanomotion. This type of nanomotion detection is referred to as optical nanomotion detection (ONMD) [32].…”
Section: Introductionmentioning
confidence: 99%